Description Of Knowledge, Self-Control, And Family Support In Adolescents in Obesity Prevention - Manik, Risda Mariana; Simanjuntak, Jesy Maria Ariani; Oktaviance, R; Ambarita, Bernadetta (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
Obesity is a condition of body weight exceeding normal limits due to the accumulation of excess fat in the body. Knowledge is the result of a person's understanding of a particular thing. Perception occurs through the five human senses, namely sight, hearing, smell, taste, and touch. Most human knowledge is obtained through the eyes and ears. Self-control is a person's ability to restrain negative reactions and control behavior caused by a stimulus so that a person can make good decisions and achieve the expected results. Family support is a process that occurs throughout the life cycle, and the nature and type of support vary at different stages of the life cycle. This study aims to determine the Description of Knowledge, Self-Control, and Family Support in Adolescents in Preventing Obesity. This study is a descriptive study with a total sampling method with a questionnaire distribution method. The sample of this study are 101 respondents. Based on this research, the results of Knowledge in Adolescents in Obesity Prevention obtained the results of the data study that: good amounted to 24 respondents (23.8%), sufficient amounted to 65 respondents (64.3%), and insufficient amounted to 12 respondents (11.9%). On average, the majority of women and men with an age range of 16 - 19 years. Self-Control in Adolescents in Obesity Prevention obtained the results of the data study that: low amounted to 67 respondents (66.3%), and high amounted to 34 respondents (33.7%). The average majority of women and men with an age range of 16 - 19 years. Family Support for Adolescents in Obesity Prevention obtained data research results that: good amounted to 87 respondents (86.1%), and less good amounted to 14 respondents (13.9%). The average majority of women and men with an age range of 16 - 19 years.